Kompetencja sądów kościelnych w Polsce do rozpatrywania spraw wiernych należących do katolickich Kościołów wschodnich (art. 16 DC) - Nowicka, Urszula (Ius Matrimoniale, 2013)
Church Tribunals in Poland shall hear and rule in the cases of the faithful belonging to the Latin Church. However, according to Art. 16 the faithful belonging to the Eastern Catholic Churches may also be subject to the competence of the Latin courts. Such competence may be either ipso iure (in a territory where the Ordinary of the Latin church has the pastoral care of the faithful of the Church sui iuris either as the only Ordinary in this area or by designation of the Apostolic See) or by reason of an extension of competence granted by the Apostolic Signatura (stably or ad casum). This publication is the analysis of such cases, which allows to conclude that applying presented criteria for Polish conditions the competence of the Tribunal of Warmia shall be indicated for the cases of the faithful belonging to the Byzanthine-Ukrainian rite, Tribunal of Siedlce for the cases of so-called Neo-Uniate, Warsaw Tribunal for the cases of the faithful belonging to other Eastern churches.